Performance of salt‐bridge microbial fuel cell (SB‐MFC) with various microorganism cultures on the generation of electricity from tofu wastewater - Dani Permana; Herlian Eriska Putra; Oman Rohman; Mahyar Ependi; Djaenudin Djaenudin (Universitas Gadjah Mada, 2024)
A suitable wastewater treatment system is required due to the high organic compound content in tofu wastewater, which can harm the environment. Biological treatment methods are effective for treating tofu wastewater due to its characteristics. Microbial fuel cells (MFCs) represent one such biological treatment option, effectively removing organic contaminants while generating low‐power electricity through bioenergetic reactions. In MFCs, microorganisms are used as biocatalysts to degrade the organic compounds present in wastewater. This study aimed to assess the efficacy of Salt‐bridge microbial fuel cells (SB‐MFC) using various acclimatized microbe cultures for reducing organic compounds and generating energy from tofu wastewater. Tofu wastewater was sterilized prior to introduction into the reactor. Additional microbes, including the native microbe consortium from tofu wastewater, Escherichia coli, Saccharomycopsis fibuligera, and a mixed culture of E. coli and S. fibuligera, were then introduced as biocatalysts. Carbon electrodes were utilized as both the anode and cathode. The results indicate that the mixed culture of E. coli and S. fibuligera significantly reduced COD and BOD5 levels, with removal rates of 82.74% and 76.53%, respectively, after 48 h. Furthermore, the culture generated a voltage of 676 mV, a current of 2.53 mA, a power density of 428 mWatt/m2, and 4.789×10‐2 kWh of energy. This study contributes to the advancement of SB‐MFC by utilizing wastewater and a combination of bacteria and yeast as biocatalysts.